(untitled) (Economic and Political Thought, 2017)
There is ample evidence of widespread inefficiency in health care systems in the early 2000s. The article is an attempt to find a balanced view on the efficiency of the Obama Healthcare Reform before it is reshaped by the new administration and the US Congress. No doubt Obamacare is a unique example of a healthcare reform. But is the reform really efficient? According to preliminary results, it achieved its goals to a certain extent, and at the same time it created a lot of new problems that should be solved. One of them, still open, is the issue of who should be in charge of the regulation of the healthcare system: to what extent the government should take part in this process; whether the shift from private to public regulation was an effective step in the development of the healthcare system; and if a free market should take place in case of such a good as healthcare. Nowadays, Obamacare is a burning topic. During his presidential campaign, Donald Trump notified that he would dismantle and/or restructure the Obama healthcare reform. Whatever the final outcome of his attempts to replace and/or to change the Affordable Care Act is going to be, it is worth assessing the health reform, which has attracted so much attention in the US and the world. The application of efficiency concepts to health care systems is a challenging topic, which raises both theoretical and practical problems. A review of input and output variables is carried out in the article. My assumption, which I will try to prove, is that the healthcare system in the USA is too expensive, and as a result it is less effective and, actually, not so ‘affordable’ as it was supposed to be.